Mechanical Vibration Mitigates the Decrease of Bone Quantity and Bone Quality of Leptin Receptor‐Deficient Db/Db Mice by Promoting Bone Formation and Inhibiting Bone Resorption. (27th July 2016) - Jing, Da; Luo, Erping; Cai, Jing; Tong, Shichao; Zhai, Mingming; Shen, Guanghao; Wang, Xin; Luo, Zhuojing
ABSTRACT: Leptin, a major hormonal product of adipocytes, is involved in regulating appetite and energy metabolism. Substantial studies have revealed the anabolic actions of leptin on skeletons and bone cells both in vivo and in vitro. Growing evidence has substantiated that leptin receptor‐deficient db/db mice exhibit decreased bone mass and impaired bone microstructure despite several conflicting results previously reported. We herein systematically investigated bone microarchitecture, mechanical strength, bone turnover and its potential molecular mechanisms in db/db mice. More importantly, we also explored an effective approach for increasing bone mass in leptin receptor‐deficient animals in an easy and noninvasive manner. Our results show that deterioration of trabecular and cortical bone microarchitecture and decreases of skeletal mechanical strength―including maximum load, yield load, stiffness, energy, tissue‐level modulus and hardness―in db/db mice were significantly ameliorated by 12‐week, whole‐body vibration (WBV) with 0.5 g, 45 Hz via micro–computed tomography (μCT), three‐point bending, and nanoindentation examinations. Serum biochemical analysis shows that WBV significantly decreased serum tartrate‐resistant acid phosphatase 5b (TRACP5b) and CTx‐1 levels and also mitigated the reduction of serum osteocalcin (OCN) in db/db mice. Bone histomorphometric analysis confirmed that decreased bone formation―lower mineral apposition rate, bone formation rate, and osteoblast numbers in cancellous bone―in db/db mice were suppressed by WBV. Real‐time PCR assays show that WBV mitigated the reductions of tibial alkaline phosphatase (ALP), OCN, Runt‐related transcription factor 2 (RUNX2), type I collagen (COL1), BMP2, Wnt3a, Lrp6, and β‐catenin mRNA expression, and prevented the increases of tibial sclerostin (SOST), RANK, RANKL, RANL/osteoprotegerin (OPG) gene levels in db/db mice. Our results show that WBV promoted bone quantity and quality in db/db mice with obvious anabolic and anticatabolic effects. This study not only enriches our basic knowledge about bone quality and bone turnover mechanisms in leptin receptor‐deficient animals, but also advances our understanding of the skeletal sensitivity of leptin‐resistant db/db mice in response to external mechanical stimulation. © 2016 American Society for Bone and Mineral Research.